Hire-Purchase Equilibria: Some Transition Theorems - Oliver, F. R. (Review of Economic Studies, 1963)
Journal Article Hire-Purchase Equilibria: Some Transition Theorems Get access F. R. Oliver F. R. Oliver Exeter Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 30, Issue 2, June 1963, Pages 131–140, https://doi.org/10.2307/2295811 Published: 01 June 1963